Major suppliers of hand-knotted carpets: India, Pakistan, China, Nepal, Egypt, Tunisia, Morocco - International Trade Center UNCTAD/GATT. (Geneva : International Trade Center UNCTAD/GATT, 1981)
This volume gives detailed information about supply position in, and export from, seven major producing countries, i.e., India, Pakistan, China, Nepal, Egypt, Tunisia, and Morocco
osc 23/07/2019
Loans
Keywords: Rug and carpet industry